Eros and allegory medieval exegesis of the Song of Songs - Turner, Denys (Specer Cistercian Publications, 1995)
The book contains an analysis of the medieval tradition of theological commentaries on the song of Songs and provides translations of a dozen medieval commentaries bever before available in English.
Includes bibliographical references and index
Review in: Theological studies, 57/3 (1996) 533-535 by E. Ann Matter.
Keywords: Bible. -- Criticism, interpretation, etc. -- History -- Middle Ages, 600-1500.